Analisis daya saing daerah dalam mendorong penanaman modal asing (PMA) di Provinsi Riau - Syahrial, Muhammad; Isyandi, Bambang; Hamidi, Wahyu (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study bertjuan to analyze regional competitiveness in encouraging foreign direct investment (FDI) in Riau Province. Having regard to the economic sectors and infrastructure base. This study uses time series data between the years 2006-2011, using the Location Question (LQ) with qualitative descriptive analysis to analyze the sectors that affect foreign investment. Results of this study showed that during the period 2006-2011 leading sectors are owned riau four sectors, namely agriculture, construction, Commerce, sector, hotels and restaurants, and the services sector.This is because the value of LQ in each of these sectors is above 1. Not all sectors of the base that is in Riau province to encourage foreign investment as the four sectors, the sector was able to absorb the non base of foreign investors to invest in the province of Riau as happened in the manufacturing sector, this is evidenced by the many processing industries are being easy target for foreign investors to invest their capital.Keywords: Competitiveness, Foreign Investment, Infrastructure